THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE OF HOUSEWIVES ON THE IMPLEMENTATION OF CLEAN AND HEALTHY LIVING BEHAVIOR IN CIPADUNG VILLAGE, CIBIRU DISTRICT, BANDUNG CITY; CROSS-SECTIONAL STUDY - Jumadiah Wardati; Eggi Indriani Pratami; Sufi Idya (International Archives of Medical Sciences and Public Health, 2026)
This study aims to identify the relationship between the level of knowledge of housewives and the implementation of Clean and Healthy Living Behavior (PHBS) in Cipadung Village, Cibiru District, Bandung City. This study used an analytical observational design with a cross-sectional approach. Data were collected from 82 respondents through a questionnaire covering 10 PHBS indicators. A statistically significant relationship was found between the level of knowledge and PHBS implementation (p < 0.05). Respondents with low knowledge may beassociated with poor PHBS implementation than respondents with good knowledge. Knowledge in this study is seen as a factor associated with PHBS implementation, not as a proven causal determinant. This study highlights the importance of health education to improve PHBS practices.